Studies on the Importance of the Cornucopia Motif in Byzantine Art and the Aniconic Decoration of the Wall Paintings of Cappadocia Region - Metin Kaya (Art-Sanat)
It is understood that the cornucopia motif, which originated in Ancient Greece, has influenced the art of many civilizations until today, especially the Roman, Byzantine, early Islamic, European and Ottoman (especially the early 18th-early 20th century ranges) artworks and it was used for the same meaning and purpose since the beginning. In addition, the studies revealed that the description of this motif as empty or full does not cause any difference in meaning, however, it is generally depicted as filled with fruits. In this article, we have identified the cornucopia motifs in the aniconic decoration of the wall paintings of nine rock churches and a rock-cut monastery monk cell, which we have examined in detail with their definitions and descriptions, and different usage examples in Byzantine art connected to their chronological framework. In addition to all these, regarding the examples we have encountered in the region, we have also emphasized how the cornucopia motif is positioned in the buildings, its decoration features, its sacred and symbolic meanings, and the relationship between architecture and art.